Paese de Cuccagna. tradições locais e regionais: a colonização italiana no alto da serra, sul do Brasil - Maria, Ilva (Organon, 2004)
Pozenato’s work, “La cuccagna”i, consists on the representation of the local imaginarium, emblematicimages from the transcultural process resulting from the culture that belongs to the Italian imigrant and theterritorial and geographic conditions of the region known as “Alto da Serra”. During the process of adaptation, itwas necessary to overcome the initial shock, when the collective myth for the paese di cuccagna was put face-to-facewith hard reality. Therefore, constructing a regional identity implies on understanding local, regional and nationaltraditions as aesthetical and cultural mediators.